KAJIAN DAMPAK PENERAPAN VARIETAS KACANG HIJAU VIMA I DAN KOMPONEN TEKNOLOGI PENDUKUNGNYA DI LAHAN SAWAH - Nila Prasetiaswati; Budhi Santosa Radjit (BUANA SAINS, 2011)
Research was conducted in Megonten village, subdistrict Kebonagung, Demak district in 2011 which is the central area of mungbean production. The research objective was to evaluate the impact of using mungbean variety Vima I and supporting technology. Data were collected by surveys, to 20 respondents are farmers cooperator farmers who have adopted the technology research conducted in 2009. The respondent was selected by purposive sampling. The data collected was assessed by using analysis of "before and after" method.. The results showed that the use of Vima I mungben variety followed by improved technology have a positive impact on increasing seed yield revenue. By 167% compared to the local variety, while costs of input was 20% higher than the traditional technology. Determinate planting through tractor (ceblok tractor) and processing of seeds with thresere can save labour costs up to 4,7%. The revenue was increase 213% and B/C ratio 3,22. The impact area of mungbean using Vima I variety increased from 12 in 2008 up to 505 ha in 2011